THE INFLUENCE OF RETAIL SERVICE QUALITY AND PRODUCT PRICES ON CONSUMER SATISFACTION AT SUZUYA PASAR ACEH BARU - Retta Marina BR Siahaan; Sukaria Sinulingga; Sugih Arto Pujangkoro (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to test and analyze the influence of retail service quality and price on consumer satisfaction at Suzuya Pasar Aceh Baru. Population of all Suzuya Pasar Aceh Baru consumers. Determining the number of samples to use the formula is 5 times the number of indicator variables, totaling 31 indicators used, totaling 155 samples. The analysis technique used is multiple linear regression analysis. The research results prove that Retail Service Quality and Price are the factors causing the decline in consumer satisfaction which has an impact on the decline in sales of Suzuya Pasar Aceh Baru. This is known from the respondents' answers where the respondents' perceptions regarding Retail Service Quality and Prices are Not Good. Personal Interaction, Promises, and Problem Solving partially do not have a significant effect on Consumer Satisfaction at Suzuya Pasar Aceh Baru. Meanwhile, Policy, Physical Appearance, Convenience, and Price show that they partially have a positive and significant effect on Consumer Satisfaction at Suzuya Pasar Aceh Baru. Simultaneous testing shows that Retail Service Quality and Price simultaneously influence Consumer Satisfaction at Suzuya Pasar Aceh Baru.